2015
DOI: 10.1016/j.freeradbiomed.2015.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 promotes survival following exposure to ionizing radiation

Abstract: NRF2 is a transcription factor that promotes antioxidant and drug-metabolizing gene expression. It also regulates the transcription of genes involved in carbohydrate and lipid metabolism, NADPH regeneration, heme and iron metabolism, as well as proteasome metabolism. Emerging research has identified NRF2 as a critical factor for promoting survival of mammalian cells subjected to ionizing radiation. At a mechanistic level, NRF2 promotes the repair of DNA damage and drives detoxification of superoxide that is ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 85 publications
3
67
0
1
Order By: Relevance
“…Recent studies have demonstrated that NRF2 promotes DNA repair and drives detoxification of superoxide that is generated after irradiation (137). In particular, NRF2 regulates the expression of RAD51, many DNA repair genes, including those of homologous recombination repair pathway, and have putative antioxidant response elements (68).…”
Section: Ionizing and Uv-radiationmentioning
confidence: 99%
“…Recent studies have demonstrated that NRF2 promotes DNA repair and drives detoxification of superoxide that is generated after irradiation (137). In particular, NRF2 regulates the expression of RAD51, many DNA repair genes, including those of homologous recombination repair pathway, and have putative antioxidant response elements (68).…”
Section: Ionizing and Uv-radiationmentioning
confidence: 99%
“…Under basal/low-stress conditions, Nrf2 is sequestered in the cytoplasm by kelch-like ECH-associated protein 1 (Keap1), an adaptor for a Cul3-based E3 ligase that promotes constitutive proteasome-mediated Nrf2 degradation (35, 36). Keap1, however, by virtue of its numerous oxidizable cysteine residues (27 in human), is capable of responding to diverse forms of oxidative stress to generate a common output, namely the activation of Nrf2 (37). This involves an increase in the levels of the Nrf2 protein and its translocation from the cytoplasm to the nucleus where it binds to antioxidant response elements (AREs) located within gene promoters.…”
Section: Nrf2 Involvement In the Early Antioxidant Responsementioning
confidence: 99%
“…In the setting of radiation, NADPH oxidase activity is increased in lung tissue 6 , which is known to enhance, and in some settings be required for, Nrf2 expression 31, 32 , presumably reducing lung injury. Studies in Nrf2 deficient mice have demonstrated a substantial increase in late lung injury after localized irradiation 33, 34 . This injury is associated with an enhanced level of isoleuvoglandin (IsoLG) modification of proteins, an event that can alter protein function 35 .…”
Section: Oxidative Stressmentioning
confidence: 99%